High-barrier full-bio-based furan copolyamide film as well as preparation method and application thereof

Through the controlled processing technology and the circulating pressurization and pressure breaking method, a fully bio-based furan copolyamide film with high gas barrier properties was prepared, which solved the problem of insufficient gas barrier properties of the existing FDCA-based polyamide film, and achieved high-performance film preparation suitable for food packaging materials.

CN119823424AActive Publication Date: 2025-04-15BEIJING UNIV OF CHEM TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510026068.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

In the prior art, the FDCA-based polyamide film has insufficient gas barrier properties and is complex in preparation process, making it difficult to meet the needs of food packaging materials.

Method used

By controlling processing processes such as temperature, pressure and time, a fully bio-based furan copolyamide film is prepared by controlling the processing technology such as temperature, pressure and time, and a stepwise cyclic pressurization and pressure breaking methods are used to form an ordered mesophase between the crystalline phase and the amorphous phase to improve gas barrier properties.

Benefits of technology

It achieves high gas barrier properties of all-bio-based furan copolyamide films, which are better than PET, PEF and MXD6 films, and are suitable for food packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823424A_ABST
    Figure CN119823424A_ABST
Patent Text Reader

Abstract

The invention discloses a high-barrier full-bio-based furan copolyamide film as well as a preparation method and application thereof, and belongs to the technical field of film manufacturing. The preparation method of the PA (XFX) 3Y film comprises the following steps: melting PA (XFX) 3Y resin slices by a hot press at a certain temperature, pressure and time, carrying out four times of heat setting under specific time and pressure, carrying out three times of pressure breaking for specific time, and naturally cooling to obtain the PA (XFX) 3Y film. The method for preparing the PA (XFX) 3Y thin film is simple, and the obtained PA (XFX) 3Y thin film shows amorphous structure characteristics, has very ideal gas barrier property and is a sustainable material applied to the field of food packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of film preparation, and in particular to a high-barrier all-bio-based furan copolyamide film and a preparation method and application thereof. Background Art

[0002] Plastics play an indispensable role in our daily lives. However, the mass production and consumption of plastics by humans has caused irreversible environmental damage and the depletion of non-renewable fossil resources. Therefore, in order to reduce dependence on fossil resources and reduce carbon dioxide emissions, the use of bio-based polymers prepared from renewable biomass raw materials to replace petroleum-based polymers prepared from petroleum-based raw materials has become a major research hotspot in academia and industry. 2,5-Furandicarboxylic acid (FDCA) is the only aromatic compound among the 12 bio-based platform compounds produced from sugars screened by the U.S. Department of Energy. FDCA is considered a good substitute for petroleum-based terephthalic acid (PTA) because of its similar structure and aromaticity to PTA. The development of FDCA-based polymers will meet the requirements of the "plastic ban" policy.

[0003] Among them, the research on FDCA-based polyesters is relatively mature, especially poly(ethylene 2,5-furandicarboxylate) (PEF), which has attracted widespread attention from all walks of life, because their gas barrier properties are better than poly(ethylene terephthalate) (PET) films, and they are more sustainable as a source of raw materials for packaging applications. As for polyamides, currently only MXD6 has good barrier properties, and the variety is single. Therefore, it is very important to develop polyamide varieties with high gas barrier properties, which are expected to become sustainable materials for food packaging applications. However, as far as FDCA-based polyamides are concerned, there are no reports on FDCA-based polyamides with excellent comprehensive performance, and there are no related studies and reports on the barrier properties of FDCA-based polyamides. The barrier properties are jointly affected by the crystalline and amorphous regions of the polymer, especially during compression molding, an ordered intermediate phase between the crystalline phase and the amorphous phase will be formed, which will better inhibit gas permeation. However, the formation of the intermediate phase will be inhibited by the crystalline region.

[0004] Existing films are usually prepared by biaxial stretching or film blowing, but the preparation steps of the above two methods are relatively complicated, and the gas barrier properties of the prepared films need to be further improved; the gas barrier properties can also be improved by adding other substances such as silicon dioxide, but this method changes the composition of the original material. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a high barrier all-bio-based furan copolyamide film and its preparation method and application. The present invention does not change the PA (XFX) 3Under the condition of Y composition, the gas barrier properties of the all-bio-based furan copolyamide film can be improved by controlling the processing technology such as temperature, pressure and time, so that it can be widely used in the field of food packaging materials.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] In one aspect, the present invention provides a method for preparing a high-barrier all-bio-based furan copolyamide film, comprising:

[0008] Step 1: Amorphous all-bio-based furan copolyamide PA (XFX) 3 Y resin slices, and then heated at a certain temperature; the temperature is between amorphous all-bio-based furan copolyamide PA (XFX) 3 Y resin is between glass transition temperature and decomposition temperature;

[0009] Step 2: Perform the first heat setting, the heat setting pressure is 15-20 MPa, the time is 10 min; then release the pressure to normal pressure and maintain it for 3 min;

[0010] Step 3: Perform a second heat-setting process, wherein the heat-setting pressure is 30-40 MPa and the time is 10 min; then release the pressure to normal pressure and maintain it for 3 min;

[0011] Step 4: Perform a third heat-setting process, wherein the heat-setting pressure is 60-80 MPa and the time is 5 min; then release the pressure to normal pressure and maintain it for 3 min;

[0012] Step 5: Perform the fourth heat-setting process, wherein the heat-setting pressure is 90-100 MPa and the time is 5 min; then release the pressure to normal pressure and maintain it for 3 min;

[0013] Step 6: After natural cooling, a fully bio-based furan copolyamide film is obtained.

[0014] Furthermore, the amorphous all-biobased furan copolyamide PA (XFX) 3 The glass transition temperature of the Y resin is ≥60°C, and the decomposition temperature is ≥380°C; the amorphous all-bio-based furan copolyamide PA (XFX) 3 The preparation method of Y resin is as follows:

[0015] (1) preparing an amino-terminated nylon active chain segment by amide ester exchange of 2,5-furandicarboxylic acid dimethyl ester and diamine X as a monomer for subsequent polymerization; the molar ratio of 2,5-furandicarboxylic acid dimethyl ester to diamine X is 3:4-3:4.2

[0016] (2) dissolving the amino-terminated active nylon chain segment obtained in (1) in a polar solvent and titrating the molecular weight with a dilute hydrochloric acid solution of a certain concentration to obtain the actual molecular weight of the nylon active chain segment;

[0017] (3) Equimolar amounts of amino-terminated nylon active chain segments and dibasic acid Y as well as a catalyst, a stabilizer, an antioxidant and an appropriate amount of water are added to a high-temperature and high-pressure reactor, and then melt-polycondensed to obtain a bio-based furan copolyamide with regular chain segments, high molecular weight, high transparency, high strength and high toughness.

[0018] Preferably, in step (1), the diamine is pentamethylenediamine or decanediamine; the dibasic acid is glutaric acid or sebacic acid; in step (2), the polar solvent is hexafluoroisopropanol or trifluoroethanol; the solubility of the dilute hydrochloric acid is 0.05-0.1 mol / L; in step (3), the catalyst is one or more of sodium hypophosphite, titanium isopropoxide, titanium citrate, triphenyl phosphite and 1,5,7-triazabicyclo[4.4.0]dec-5-ene; the antioxidant is antioxidant 1010 or antioxidant 1098; and the stabilizer is stabilizer SEED.

[0019] The molar ratio of dimethyl 2,5-furandicarboxylate to diamine X is 3:4-3:4.2; the amorphous all-bio-based furan copolyamide PA (XFX) 3 The specific structure of Y resin is as follows:

[0020] ;

[0021] Wherein, X is a linear aliphatic diamine such as pentamethylenediamine or decanediamine; and Y is a bio-based dibasic acid such as glutaric acid or sebacic acid.

[0022] Furthermore, the step (1) is specifically as follows: dimethyl 2,5-furandicarboxylate and a slightly excess amount of diamine X are added to a glass kettle equipped with a mechanical stirrer and a condenser, and the temperature is raised to 120°C for reaction for 2 hours under nitrogen flow, i.e., normal pressure. During this stage, a large amount of methanol is produced. The temperature is then raised to 160-190°C for reaction for 1-2 hours, and then raised to 210°C for reaction for 0.5 hours. During these two temperature stages, only a small amount of methanol is produced. Finally, the reaction is carried out under vacuum at -0.07 MPa for 15 minutes to remove the remaining small molecules, thereby obtaining an amino-terminated active nylon segment.

[0023] Preferably, in step (2), the polar solvent is one of hexafluoroisopropanol and trifluoroethanol, and the concentration of dilute hydrochloric acid is 0.05-0.1 mol / L.

[0024] Furthermore, the step (2) is specifically as follows: 0.2-0.4 g of the nylon active chain segment is placed in a 100 mL beaker, 30-50 mL of a polar solvent is added and stirred for 0.5-2 h to dissolve, and then the mixture is placed in an automatic potentiometric titrator and titrated with a dilute hydrochloric acid solution of a certain concentration while stirring to obtain the actual molecular weight of the nylon active chain segment.

[0025] Preferably, in step (3), the amount of the catalyst is 2‰ of the total mass of the nylon active chain segment and the dibasic acid. The amount of the antioxidant is 1‰ of the total mass of the nylon active chain segment and the dibasic acid; and the amount of the stabilizer is 1‰ of the total mass of the nylon active chain segment and the dibasic acid.

[0026] Furthermore, in the step (3), the specific steps for preparing the bio-based furan copolyamide are: calculating the molar number of the nylon active chain segment by the actual molecular weight of the nylon active chain segment titrated in (2). Then, equal moles of the nylon active chain segment and the dibasic acid Y as well as the catalyst, stabilizer, antioxidant and appropriate amount of water are added to a high temperature and high pressure reactor, the air is first replaced by nitrogen, and then the temperature is raised to 5-10°C above the melting point of the dibasic acid Y and stabilized for 0.5-2 h, then reacted at 190-220°C for 2 h, and then the small molecules in the system are slowly released at 220-230°C, and then reacted at 230°C and 0 MPa for 1-2 h, and finally reacted at 240-250°C and -0.09 MPa for 1-2 h to complete the polymerization. The system is restored to normal pressure, the reactor is opened, the bio-based furan copolyamide is quickly taken out and placed in deionized water, and then the bio-based furan copolyamide product is placed in a 60°C forced air drying oven and dried for 24 h.

[0027] On the other hand, the present invention also provides a high-barrier all-bio-based furan copolyamide film prepared by the above method.

[0028] In another aspect, the present invention also provides an application of the above-mentioned high-barrier all-bio-based furan copolyamide film in food packaging materials, which can be used for food packaging film bags, food packaging boxes or food packaging bottles. The gas barrier property of the prepared all-bio-based furan copolyamide film is better than that of PEF, PET, and even MXD6.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] Fully bio-based furan copolyamide PA (XFX) prepared by the present invention 3 The Y film exhibits amorphous structural characteristics and has very excellent gas barrier properties. It can be used in the field of food packaging materials, including food packaging film bags, food packaging boxes, and food packaging bottles.

[0031] The method of the present invention does not change the all-bio-based furan copolyamide PA (XFX) 3Under the condition of Y resin composition, the prepared all-bio-based furan copolyamide PA (XFX) is prepared by controlling the processing technology such as temperature, pressure and time. 3 Y film has excellent gas barrier properties. The present invention is different from the conventional compression molding process in that by gradually increasing pressure for a certain period of time and breaking pressure for a certain period of time, PA (XFX) 3 The disordered hydrogen bonds in Y are rearranged, and the interaction between the molecular chains is enhanced to form an ordered intermediate phase between the amorphous phase and the crystalline phase. At the same time, through this cyclic pressurization and depressurization method, the arrangement of this ordered intermediate phase can be maximized, thereby more effectively hindering the passage of gas. In addition, maximizing the arrangement of the ordered intermediate phase can improve the bio-based furan copolyamide PA (XFX) 3 The glass transition temperature of the Y film makes it in the glass state as early as possible, the free volume is frozen and kept at the minimum value, there is not enough space for the molecular chain to move, and it also makes it difficult for gas molecules to diffuse. These four cycles of pressurization, shaping and pressure relief finally obtained the high barrier all-bio-based furan copolyamide PA (XFX) 3 Y film.

[0032] Compared with the prior art, the present invention provides a method for preparing a high-barrier all-bio-based furan copolyamide film, which uses a simple processing technology to make it have very excellent gas barrier properties, which is better than PET, PEF, and even MXD6. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 PA(5F5) in Example 1 3 DSC curves before and after 5-cycle compression molding;

[0034] Figure 2 PA(5F5) in Example 1 3 XRD spectra before and after 5-cycle compression molding. DETAILED DESCRIPTION

[0035] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0036] In the present invention, the materials and reagents used can be obtained from commercial sources unless otherwise specified.

[0037] The present invention provides a high-barrier all-biobased furan copolyamide film and a preparation method and application thereof, and specific embodiments are as follows.

[0038] Example 1

[0039] A method for preparing a high-barrier all-biobased furan copolyamide film, comprising:

[0040] Step 1: 30 g PA(5F5) at normal pressure 3 5. The resin slices were melted at 255 °C for 30 min;

[0041] Step 2: The first heat setting temperature is 255 °C, the pressure is 15 MPa, and the time is 10 min; then the pressure is released to normal pressure and maintained for 3 min;

[0042] Step 3: The second heat setting temperature is 255 °C, the pressure is 30 MPa, and the time is 10 min; then the pressure is released to normal pressure and maintained for 3 min;

[0043] Step 4: The third heat setting temperature is 255 °C, the pressure is 60 MPa, and the time is 5 min; then the pressure is released to normal pressure and maintained for 3 min;

[0044] Step 5: The fourth heat setting temperature is 255 °C, the pressure is 90 MPa, and the time is 5 min; then the pressure is released to normal pressure;

[0045] Step 6: After natural cooling, a fully bio-based furan copolyamide film is obtained.

[0046] Above PA (5F5) 3 5 The resin was prepared by the following method:

[0047] (1) 184.15 parts of dimethyl 2,5-furandicarboxylate and 143.05 parts of pentamethylenediamine were added to a glass kettle equipped with a magnetic stirring device and a condensing device, wherein the molar ratio of dimethyl 2,5-furandicarboxylate to pentamethylenediamine was 3:4.2; the temperature was raised to 120°C for reaction for 2 h under nitrogen flow, i.e., normal pressure. During this stage, a large amount of methanol was produced. The temperature was then raised to 190°C for reaction for 2 h, and then raised to 210°C for reaction for 0.5 h. During these three temperature stages, only a small amount of methanol was produced. Finally, the reaction was carried out under vacuum at -0.07 MPa for 15 min to remove the remaining small molecules, thereby obtaining an amino-terminated active nylon segment (5F5) 3 ;

[0048] (2) 0.3 parts (5F5) 3 Dissolve in 30 mL of hexafluoroisopropanol, stir until dissolved, and titrate with 0.05 mol / L dilute hydrochloric acid solution using an automatic potentiometric titrator to obtain (5F5) 3 The actual average molecular weight of the diamine is 780 g / mol;

[0049] (3) 100 copies (5F5) 316.94 parts of glutaric acid, 0.234 parts of catalyst sodium hypophosphite, 0.117 parts of antioxidant 1010, 0.117 parts of stabilizer SEED and 5.847 parts of deionized water were added to a high temperature and high pressure reactor, wherein (5F5) 3 The molar ratio of glutaric acid to adipic acid is 1:1; the air is first replaced by nitrogen, then the temperature is raised to 5-10 ℃ above the melting point of adipic acid, that is, 160℃ for 1 hour, then reacted at 230℃ for 2 hours, and then the small molecules in the system are slowly released at 230℃; then reacted at 240℃ and 0 MPa for 1 hour, and finally reacted at 250℃ and -0.09 MPa for 1 hour to complete the polymerization. The system is restored to normal pressure, the reactor is opened, the bio-based furan copolyamide is quickly taken out and placed in deionized water, and then the bio-based furan copolyamide product is placed in a 60℃ forced air drying oven for 24 hours.

[0050] Example 2

[0051] A method for preparing a high-barrier all-biobased furan copolyamide film, comprising:

[0052] Step 1: 30 g PA(5F5) at normal pressure 3 10 The resin slices were melted at 245 °C for 25 min;

[0053] Step 2: Except that the temperature of the fourth heat setting is 245°C, other process conditions are the same as those in Example 1.

[0054] Above PA (5F5) 3 10 The resin was prepared by the following method:

[0055] (1)-(2) The same preparation method as in Example 1 was used to obtain (5F5) 3 The molecular weight of the diamine is 780 g / mol;

[0056] (3) 100 copies (5F5) 3 Diamine and 25.93 parts of sebacic acid, 0.252 parts of catalyst triphenyl phosphite, 0.126 parts of antioxidant 1098, 0.126 parts of stabilizer SEED and 6.30 parts of deionized water were added to a high temperature and high pressure reactor, and then the temperature was raised to 5-10 ℃ above the melting point of sebacic acid, that is, 140 ℃ for stabilization for 1 hour, followed by reaction at 220 ℃ for 2 hours, and then the small molecules in the system were slowly released at 220 ℃; then the reaction was carried out at 230 ℃ and 0 MPa for 1 hour, and finally at 240 ℃ and -0.09 MPa for 1 hour to complete the polymerization. The system was restored to normal pressure, the reactor was opened, the bio-based furan copolyamide was quickly taken out and placed in deionized water, and then the bio-based furan copolyamide product was placed in a 60 ℃ forced air drying oven for 24 hours.

[0057] Example 3

[0058] A method for preparing a high-barrier all-biobased furan copolyamide film, comprising:

[0059] Step 1: 30 g PA (10F10) at normal pressure 3 5. The resin slices were melted at 240 °C for 20 min;

[0060] Step 2: Except that the temperature of the fourth heat setting is 240°C, other process conditions are the same as those in Example 1.

[0061] The above PA (10F10) 3 5 The resin was prepared by the following method:

[0062] (1) 184.15 parts of dimethyl 2,5-furandicarboxylate and 241.23 parts of decanediamine were added to a glass kettle equipped with a magnetic stirring device and a condensing device. The temperature was raised to 140°C for reaction for 2 h under nitrogen flow, i.e., normal pressure. During this stage, a large amount of methanol was produced. The temperature was then raised to 200°C for reaction for 2 h, and then raised to 220°C for reaction for 0.5 h. Only a small amount of methanol was produced during these three temperature stages. Finally, the reaction was carried out in a vacuum at -0.07 MPa for 15 min to remove the remaining small molecules, thereby obtaining an amino-terminated active nylon segment with three repeating units (10F10 (3) diamine).

[0063] (2) Add 0.3 parts of 10F10 (3) The diamine was dissolved in 30 mL of hexafluoroisopropanol and stirred until dissolved. It was titrated with 0.05 mol / L dilute hydrochloric acid solution using an automatic potentiometric titrator to obtain 10F10 (3) The actual average molecular weight of the diamine is 1034 g / mol

[0064] (3) 100 portions of 10F10 (3) Diamine and 12.78 parts of glutaric acid, 0.226 parts of catalyst titanium citrate, 0.113 parts of antioxidant 1098, 0.113 parts of stabilizer SEED and 5.64 parts of deionized water were added to a high temperature and high pressure reactor, and the air was first replaced by nitrogen, and then the temperature was raised to 5-10 ℃ above the melting point of adipic acid, that is, 160 ℃ for stabilization for 1 hour, and then reacted at 220 ℃ for 2 hours, and then the small molecules in the system were slowly released at 220 ℃; then reacted at 230 ℃ and 0 MPa for 1 hour, and finally reacted at 240 ℃ and -0.09 MPa for 1 hour to complete the polymerization. The system was restored to normal pressure, the reactor was opened, the bio-based furan copolyamide was quickly taken out and placed in deionized water, and then the bio-based furan copolyamide product was placed in a 60 ℃ forced air drying oven for 24 hours.

[0065] Example 4

[0066] A method for preparing a high-barrier all-biobased furan copolyamide film, comprising:

[0067] Step 1: 30 g PA (10F10) at normal pressure 3 10 The resin slices were melted at 230 °C for 15 min;

[0068] Step 2: Except that the temperature of the fourth heat setting is 230°C, other process conditions are the same as those in Example 1.

[0069] The above PA (10F10) 3 10 The resin was prepared by the following method:

[0070] (1)-(2) Same as Example 3, 10F10 is obtained (3) The molecular weight of the diamine is 1034 g / mol;

[0071] (3) 100 portions of 10F10 (3) Diamine and 19.56 parts of sebacic acid, 0.240 parts of catalyst 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 0.120 parts of antioxidant 1010, 0.120 parts of stabilizer SEED and 5.98 parts of deionized water were added to a high temperature and high pressure reactor, and the air was first replaced by nitrogen, and then the temperature was raised to 5-10 ℃ above the melting point of adipic acid, that is, 160 ℃ for stabilization for 1 hour, and then reacted at 220 ℃ for 2 hours, and then the small molecules in the system were slowly released at 220 ℃; then reacted at 230 ℃ and 0MPa for 1 hour, and finally reacted at 240 ℃ and -0.09 MPa for 1 hour to complete the polymerization. The system was restored to normal pressure, the reactor was opened, the bio-based furan copolyamide was quickly taken out and placed in deionized water, and then the bio-based furan copolyamide product was placed in a 60 ℃ forced air drying oven for 24 hours.

[0072] Example 5

[0073] A method for preparing a high-barrier all-biobased furan copolyamide, comprising:

[0074] (1) 30 g PA (5F5) 3 5. The resin slices were melted at 255 °C for 30 min;

[0075] (2) The first heat setting temperature is 255 °C, the pressure is 20 MPa, and the time is 10 min; the first pressure breaking time is 3 min and the pressure is normal pressure.

[0076] (3) The second heat setting temperature is 255 °C, the pressure is 40 MPa, and the time is 10 min; the second pressure breaking time is 3 min and the pressure is normal pressure.

[0077] (4) The third heat setting temperature is 255 °C, the pressure is 80 MPa, and the time is 5 min; the third pressure breaking time is 3 min and the pressure is normal pressure.

[0078] (5) The fourth heat setting temperature is 255 °C, the pressure is 100 MPa, and the time is 5 min;

[0079] (6) After natural cooling, a fully bio-based furan copolyamide film is obtained.

[0080] Above PA (5F5) 3 5 The resin preparation method is the same as in Example 1.

[0081] To further illustrate the beneficial effects of the present invention, a comparative example is constructed as follows:

[0082] Comparative Example 1

[0083] A method for preparing a thin film, comprising:

[0084] Step 1: 30 g PA(5F5) 3 5. The resin slices were melted at 255 °C for 30 min;

[0085] Step 2: heat setting temperature is 255 °C, pressure is 90 MPa, and time is 10 min;

[0086] Step 3: After natural cooling, a fully bio-based furan copolyamide film is obtained.

[0087] Above PA (5F5) 3 5 The resin preparation method is the same as in Example 1.

[0088] Comparative Example 2

[0089] A method for preparing a thin film, comprising:

[0090] Step 1: 30 g PA(5F5) 3 10 The resin slices were melted at 245 °C for 25 min;

[0091] Step 2: heat setting temperature is 245 °C, pressure is 90 MPa, and time is 10 min;

[0092] Step 3: After natural cooling, a fully bio-based furan copolyamide film is obtained.

[0093] Above PA (5F5) 310 The resin preparation method is the same as that in Example 2.

[0094] Comparative Example 3

[0095] A method for preparing a thin film, comprising:

[0096] Step 1: 30 g PA (10F10) 3 5. The resin slices were melted at 240 °C for 20 min;

[0097] Step 2: heat setting temperature is 245 °C, pressure is 90 MPa, and time is 10 min;

[0098] Step 3: After natural cooling, a fully bio-based furan copolyamide film is obtained.

[0099] The above PA (10F10) 3 5 The resin preparation method is the same as in Example 3.

[0100] Comparative Example 4

[0101] A method for preparing a thin film, comprising:

[0102] Step 1: 30 g PA (10F10) 3 10 The resin slices were melted at 230 °C for 15 min;

[0103] Step 2: heat setting temperature is 245 °C, pressure is 90 MPa, and time is 10 min;

[0104] Step 3: After natural cooling, a fully bio-based furan copolyamide film is obtained.

[0105] The above PA (10F10) 3 10 The resin preparation method is the same as that in Example 4.

[0106] Comparative Example 5

[0107] A method for preparing a thin film, comprising:

[0108] Step 1: 30 g PA(5F5) 3 5. The resin slices were melted at 255 °C for 30 min;

[0109] Step 2: The first heat setting temperature is 255 °C, the pressure is 15 MPa, and the time is 10 min;

[0110] Step 3: The second heat setting temperature is 255 °C, the pressure is 30 MPa, and the time is 10 min;

[0111] Step 4: The third heat setting temperature is 255 °C, the pressure is 60 MPa, and the time is 5 min;

[0112] Step 5: The fourth heat setting temperature is 255 °C, the pressure is 90 MPa, and the time is 5 min;

[0113] Step 6: After natural cooling, a fully bio-based furan copolyamide film is obtained.

[0114] Above PA (5F5) 3 5 The resin preparation method is the same as in Example 1.

[0115] Comparative Example 6

[0116] A method for preparing a thin film, comprising:

[0117] Step 1: 30 g PA(5F5) 3 10 The resin slices were melted at 245 °C for 25 min;

[0118] Step 2: The first heat setting temperature is 245 °C, the pressure is 15 MPa, and the time is 10 min;

[0119] Step 3: The second heat setting temperature is 245 °C, the pressure is 30 MPa, and the time is 10 min;

[0120] Step 4: The third heat setting temperature is 245 °C, the pressure is 60 MPa, and the time is 5 min;

[0121] Step 5: The fourth heat setting temperature is 245 °C, the pressure is 90 MPa, and the time is 5 min;

[0122] Step 6: After natural cooling, a fully bio-based furan copolyamide film is obtained.

[0123] Above PA (5F5) 3 10 The resin preparation method is the same as that in Example 2.

[0124] Comparative Example 7

[0125] A method for preparing a thin film, comprising:

[0126] Step 1: 30 g PA (10F10) 3 5. The resin slices were melted at 240 °C for 20 min;

[0127] Step 2: The first heat setting temperature is 240 °C, the pressure is 15 MPa, and the time is 10 min;

[0128] Step 3: The second heat setting temperature is 240 °C, the pressure is 30 MPa, and the time is 10 min;

[0129] Step 4: The third heat setting temperature is 240 °C, the pressure is 60 MPa, and the time is 5 min;

[0130] Step 5: The fourth heat setting temperature is 240 °C, the pressure is 90 MPa, and the time is 5 min;

[0131] Step 6: After natural cooling, a fully bio-based furan copolyamide film is obtained.

[0132] The above PA (10F10) 3 5 The resin preparation method is the same as in Example 3.

[0133] Comparative Example 8

[0134] A method for preparing a thin film, comprising:

[0135] Step 1: 30 g PA (10F10) 3 10 The resin slices were melted at 230 °C for 15 min;

[0136] Step 2: The first heat setting temperature is 230 °C, the pressure is 15 MPa, and the time is 10 min;

[0137] Step 3: The second heat setting temperature is 230 °C, the pressure is 30 MPa, and the time is 10 min;

[0138] Step 4: The third heat setting temperature is 230 °C, the pressure is 60 MPa, and the time is 5 min;

[0139] Step 5: The fourth heat setting temperature is 230 °C, the pressure is 90 MPa, and the time is 5 min;

[0140] Step 6: After natural cooling, a fully bio-based furan copolyamide film is obtained.

[0141] The above PA (10F10) 3 10 The resin preparation method is the same as that in Example 4.

[0142] Comparative Example 9

[0143] A method for preparing a thin film, comprising:

[0144] (1) 30 g of PET resin chips were melted at 270 °C for 30 min;

[0145] (2) The first heat setting temperature is 270 °C, the pressure is 15 MPa, and the time is 10 min; the first pressure-breaking time is 3 min;

[0146] (3) The second heat setting temperature is 270 °C, the pressure is 30 MPa, and the time is 10 min; the second pressure-breaking time is 3 min;

[0147] (4) The third heat setting temperature is 270 °C, the pressure is 60 MPa, and the time is 5 min; the third pressure-breaking time is 3 min;

[0148] (5) The fourth heat setting temperature is 270 °C, the pressure is 90 MPa, and the time is 5 min;

[0149] (6) After natural cooling, a PET film is obtained.

[0150] Comparative Example 10

[0151] (1) 30 g of PEF resin chips were melted at 245 °C for 30 min;

[0152] (2) The first heat setting temperature is 245 °C, the pressure is 15 MPa, and the time is 10 min; the first pressure-breaking time is 3 min;

[0153] (3) The second heat setting temperature is 245 °C, the pressure is 30 MPa, and the time is 10 min; the second pressure-breaking time is 3 min;

[0154] (4) The third heat setting temperature is 245 °C, the pressure is 60 MPa, and the time is 5 min; the third pressure-breaking time is 3 min;

[0155] (5) The fourth heat setting temperature is 245 °C, the pressure is 90 MPa, and the time is 5 min;

[0156] (6) After natural cooling, the PEF film is obtained.

[0157] Comparative Example 11

[0158] A method for preparing a thin film, comprising:

[0159] (1) 30 g of MXD6 resin chips were melted at 260 °C for 30 min;

[0160] (2) The first heat setting temperature is 260 °C, the pressure is 15 MPa, and the time is 10 min; the first pressure-breaking time is 3 min;

[0161] (3) The second heat setting temperature is 260 °C, the pressure is 30 MPa, and the time is 10 min; the second pressure-breaking time is 3 min;

[0162] (4) The third heat setting temperature is 260 °C, the pressure is 60 MPa, and the time is 5 min; the third pressure-breaking time is 3 min;

[0163] (5) The fourth heat setting temperature is 260 °C, the pressure is 90 MPa, and the time is 5 min;

[0164] (6) After natural cooling, the MXD6 film is obtained.

[0165] Comparative Example 12

[0166] In this comparative example, the first heat setting pressure is 10 MPa, and the other conditions are the same as those in Example 1.

[0167] Comparative Example 13

[0168] In this comparative example, the first heat setting pressure is 25 MPa, and the other conditions are the same as those in Example 1.

[0169] Comparative Example 14

[0170] In this comparative example, the second heat setting pressure is 50 MPa, and the other conditions are the same as those in Example 1.

[0171] Comparative Example 15

[0172] In this comparative example, the second heat setting pressure is 25 MPa, and the other conditions are the same as those in Example 1.

[0173] Comparative Example 16

[0174] In this comparative example, the third heat setting pressure is 90 MPa, and the other conditions are the same as those in Example 1.

[0175] Comparative Example 17

[0176] In this comparative example, the third heat setting pressure is 50 MPa, and the other conditions are the same as those in Example 1.

[0177] Comparative Example 18

[0178] In this comparative example, the fourth heat setting pressure is 110 MPa, and the other conditions are the same as those in Example 1.

[0179] Comparative Example 19

[0180] In this comparative example, the fourth heat setting pressure is 85 MPa, and the other conditions are the same as those in Example 1.

[0181] The barrier properties of the films prepared in the examples and comparative examples were tested using a VAC-V2 differential pressure gas permeometer. 2 The sample diameter is 13 mm, O 2 The sample diameter is 75 mm and the thickness is 1 mm. The test temperature is 23 ℃±2 ℃, the humidity is 49±1 %RH, 1 barrer=10 –10 cm 3 cm / cm 2 ·s·cmHg. See Table 1-3 for specific test results.

[0182] About PA(XFX) 3 The glass transition temperature of Y resin and the film prepared by compression was measured by differential scanning calorimetry (DSC). Figure 1 and Table 1-3; for PA (XFX) 3 The XRD results of Y resin and the film prepared by compression are shown in Figure 2 and Tables 1-3.

[0183] Table 1

[0184]

[0185] Depend on Figure 1-2 As shown in Table 1, the molecular interaction force of the film prepared by the method of the present invention is stronger than that of the film before compression. 3 Y resin is strong, and the glass transition temperature increases by about 10°C. PA (XFX) 3 The disordered hydrogen bonds between the Y molecular chains are rearranged to maximize the orderly arrangement of the intermediate phase, which has excellent gas barrier properties, and the oxygen gas barrier property is as low as 0.0003×10 –10 cm 3 cm / cm 2 ·s·cmHg, carbon dioxide gas barrier property 0.0015×10 –10 cm 3 cm / cm 2 ·s·cmHg.

[0186] Table 2

[0187]

[0188] From Table 1-2, it can be found that if the all-bio-based furan copolyamide PA (XFX) 3 The Y film adopts the conventional compression molding method, without the step-by-step cycle of pressurization and depressurization, and its oxygen and carbon dioxide gas permeability coefficients will be poor. This is because amorphous PA (XFX) 3The disordered hydrogen bonds between Y molecular chains cannot be fully arranged, the interaction force between molecular chains is relatively small, and the glass transition temperature only increases by 1-2 °C.

[0189] Comparing Examples 1-5 and Comparative Examples 5-8, it can be found that if the all-bio-based furan copolyamide PA (XFX) 3 The Y film only uses the method of gradual pressure increase without breaking the pressure, and its oxygen and carbon dioxide gas permeability coefficients will be relatively poor. This is because gradual pressure increase can make amorphous PA (XFX) 3 The disordered hydrogen bonds between Y molecular chains can be rearranged, the interaction force between molecular chains is relatively enhanced, and the glass transition temperature increases by 4-6 °C. However, the ordered intermediate phase arrangement formed cannot be maximized.

[0190] By comparing Examples 1-5 and Comparative Examples 9-11, it can be found that the all-bio-based furan copolyamide PA (XFX) obtained by the step-by-step cycle pressurization and depressurization method is 3 The gas barrier property of Y film is one order of magnitude higher than that of PET film, PEF film and even MXD6 film obtained by the same method.

[0191] Table 3

[0192]

[0193] As shown in Table 3, by comparing Example 1 with Comparative Examples 12-19, it can be found that as long as one step does not reach the specified pressure, the obtained all-bio-based furan copolyamide PA (XFX) 3 The gas barrier properties of Y films are not as good as those of all-bio-based furan copolyamide PA (XFX) obtained by cyclic pressurization and depressurization under specific pressure and specific time. 3 The gas barrier properties of Y film are good, but they are lower than those of all-bio-based furan copolyamide PA (XFX) obtained by conventional compression molding. 3 Y film has good gas barrier properties.

[0194] The pressure of the first heat setting is small (Comparative Example 12) or too large (Comparative Example 13), the glass transition temperature of the obtained film is not much different from that of the resin material, and the barrier performance of the prepared film is also deteriorated. This may be because when the pressure is too small, the molecular chains cannot be fully arranged and the bubbles cannot be well removed; when the pressure is too large, it may cause overflow and waste of resources, and the film preparation is incomplete and prone to wrinkles. The gas barrier properties of the prepared films are different when the pressure of the subsequent three heat setting processes is too large or too small (Comparative Examples 14-19), but they are all much lower than the performance of the film prepared in Example 1 of the present invention.

[0195] In summary, the present invention designs an amorphous all-bio-based furan copolyamide PA (XFX) 3Y, making it have excellent gas barrier properties. At the same time, without changing the all-bio-based furan copolyamide PA (XFX) 3 Under the condition of Y resin composition, the all-bio-based furan copolyamide PA (XFX) was prepared by controlling the processing technology such as temperature, pressure and time, and using step-by-step cycle pressurization and depressurization. 3 Y film has better gas barrier properties and can be used in the field of food packaging materials, including food packaging film bags, food packaging boxes, and food packaging bottles.

[0196] The above is a preferred embodiment of the present invention. For ordinary technicians in this technical field, making several improvements and modifications without departing from the principles of the present invention should also be regarded as within the protection scope of the present invention.

Claims

1. A method for preparing a high-barrier all-biobased furan copolyamide film, characterized in that: include: Step 1: Slice the amorphous all-bio-based furan copolyamide PA (XFX) 3Y resin, and then heat it at a certain temperature; the temperature is between the glass transition temperature and the decomposition temperature of the amorphous all-bio-based furan copolyamide PA (XFX) 3Y resin; Step 2: Perform the first heat setting, the heat setting pressure is 15-20 MPa, the time is 10 min; then release the pressure to normal pressure and maintain it for 3 min; Step 3: Perform a second heat-setting process, wherein the heat-setting pressure is 30-40 MPa and the time is 10 min; then release the pressure to normal pressure and maintain it for 3 min; Step 4: Perform a third heat-setting process, wherein the heat-setting pressure is 60-80 MPa and the time is 5 min; then release the pressure to normal pressure and maintain it for 3 min; Step 5: Perform the fourth heat-setting process, wherein the heat-setting pressure is 90-100 MPa and the time is 5 min; then release the pressure to normal pressure and maintain it for 3 min; Step 6: After natural cooling, a fully bio-based furan copolyamide film is obtained.

2. The method according to claim 1, characterized in that The glass transition temperature of the amorphous all-bio-based furan copolyamide PA (XFX) 3Y resin is ≥60°C, and the decomposition temperature is ≥380°C. The preparation method of the amorphous all-bio-based furan copolyamide PA (XFX) 3Y resin is as follows: (1) under nitrogen protection, adding dimethyl 2,5-furandicarboxylate and diamine into a glass kettle, heating the reaction several times, and preparing an amino-terminated active nylon segment; the molar ratio of dimethyl 2,5-furandicarboxylate to diamine is 3:4-3:4.2; (2) dissolving the active nylon chain segment obtained in step (1) in a polar solvent, and then titrating the molecular weight with a dilute hydrochloric acid solution to obtain the actual molecular weight of the nylon active chain segment; (3) adding the active nylon segment and dibasic acid obtained in step (1) together with a catalyst, an antioxidant, a stabilizer and an appropriate amount of water into a high-temperature and high-pressure reactor, replacing the air with nitrogen, and then obtaining a bio-based furan copolyamide by melt polycondensation; The molar ratio of the active nylon chain segment to the dibasic acid is 1:

1.

3. The preparation method according to claim 2, characterized in that: In the step (1), the diamine is pentamethylenediamine or decanediamine; the dibasic acid is glutaric acid or sebacic acid; in the step (2), the polar solvent is hexafluoroisopropanol or trifluoroethanol; the solubility of the dilute hydrochloric acid is 0.05-0.1 mol / L; in the step (3), the catalyst is one or more of sodium hypophosphite, titanium isopropoxide, titanium citrate, triphenyl phosphite and 1,5,7-triazabicyclo[4.4.0]dec-5-ene; the antioxidant is antioxidant 1010 or antioxidant 1098; and the stabilizer is stabilizer SEED.

4. The preparation method according to claim 2, characterized in that: The step (1) is specifically as follows: adding dimethyl 2,5-furandicarboxylate and a diamine in a defined molar ratio into a glass kettle equipped with a mechanical stirrer and a condenser, heating to 120°C for reaction for 2 h under nitrogen flow, i.e., normal pressure, then heating to 160-190°C for reaction for 1-2 h, then heating to 210°C for reaction for 0.5 h, and finally reacting in vacuum at -0.07 Mpa for 15 min, thereby obtaining an amino-terminated active nylon chain segment.

5. The preparation method according to claim 4, characterized in that: The step (2) is specifically as follows: 0.2-0.4 g of the nylon active chain segment is placed in a 100 mL beaker, 30-50 mL of a polar solvent is added and stirred for 0.5-2 h to dissolve, and then the mixture is placed in an automatic potentiometric titrator and titrated with a dilute hydrochloric acid solution of a certain concentration while stirring to obtain the actual molecular weight of the nylon active chain segment.

6. The preparation method according to claim 5, characterized in that: In the step (3), the amount of the catalyst is 2‰ of the total mass of the nylon active chain segment and the dibasic acid; the amount of the antioxidant is 1‰ of the total mass of the nylon active chain segment and the dibasic acid; and the amount of the stabilizer is 1‰ of the total mass of the nylon active chain segment and the dibasic acid.

7. The preparation method according to claim 6, characterized in that: The step (3) is specifically as follows: the molar number of the nylon active chain segment is calculated by the actual molecular weight of the nylon active chain segment titrated in (2); then, equal moles of the nylon active chain segment and the dibasic acid as well as the catalyst, stabilizer, antioxidant and appropriate amount of water are added into a high temperature and high pressure reactor, the air is first replaced by nitrogen, then the temperature is raised to 5-10°C above the melting point of the dibasic acid and stabilized for 0.5-2 h, then the reaction is carried out at 190-220°C for 2 h, then the small molecules in the system are slowly released at 220-230°C, then the reaction is carried out at 230°C and 0 MPa for 1-2 h, and finally the reaction is carried out at 240-250°C and -0.09 MPa for 1-2 h to complete the polymerization; the system is restored to normal pressure, the reactor is opened, the bio-based furan copolyamide is quickly taken out and placed in deionized water, and then the bio-based furan copolyamide product is placed in a 60°C forced air drying oven and dried for 24 h.

8. A high barrier all-biobased furan copolyamide film, characterized in that: Prepared according to any one of claims 1 to 7.

9. Use of the high barrier all-biobased furan copolyamide film according to claim 8 in food packaging materials.

10. The use according to claim 9, characterized in that: The food packaging material includes a food packaging film bag, a food packaging box or a food packaging bottle.

Citation Information

Patent Citations

  • Preparation method of high molecular weight furan polyamide

    CN113429569A

  • Preparation method of single-layer furyl nylon film

    CN118144140A

  • Novel bio-based furan copolyamide and preparation method thereof

    CN118834384A

  • Polyamide films with high oxygen barrier

    EP3418316A1

  • Multilayer molded article

    JP2018051840A